Lower Extremity Amputations: Factors Associated With Mortality or Contralateral Amputation. (November 2013) - Shah, Samir K.; Bena, James F.; Allemang, Matthew T.; Kelso, Rebecca; Clair, Daniel G.; Vargas, Lina; Kashyap, Vikram S.
Background: Tissue loss or gangrene in the setting of lower extremity peripheral artery disease (PAD) may result in amputation. Previous studies have demonstrated elevated mortality rates after major transtibial and transfemoral amputation. Also, amputation of 1 leg may be associated with subsequent major amputation of the contralateral leg. The aim of our study was to identify patient variables associated with mortality and contralateral amputation. Methods: We reviewed the medical records of patients who underwent transfemoral or transtibial amputation secondary to PAD from 2004 to 2009. A total of 454 consecutive major amputations were performed on 391 patients, with 63 of these having a subsequent contralateral amputation. Standard demographic information, comorbidities, prior vascular interventions, and relevant procedural information were extracted from patient records. Kaplan-Meier estimates of survival were calculated. Cox proportional hazard models were used to estimate the risk of death and contralateral amputation. Multivariate Cox proportional hazards models were fit for all variables shown to be marginally associated in the univariate model. Results: In 391 amputees, the mean age was 67.3 years, 63% were male and 62% were caucasian. Patients had high rates of diabetes (63%), hypertension (83%), renal insufficiency (35%), hyperlipidemia (51%), and prior ipsilateral vascular intervention (75%). Seventy percent of patients had below-knee amputations. Perioperative mortality was 9.2% (n = 36). Survival at 12 and 24 months was 70% (95% confidence interval [CI], 65%-74%) and 60% (95% CI, 55%-65%), respectively. Multivariate analysis demonstrated that several independent factors were detrimental to survival including chronic obstructive pulmonary disease (hazard ratio [HR] 1.82, P = .002), dialysis dependence (HR 2.50, P < .001), high cardiac risk (HR 2.20, P < .001), and guillotine amputation (HR 2.49, P = .004). Dialysis (HR 2.42, P = .002) and revision of the index ipsilateral amputation to a higher level (HR 2.02, P = .014) were associated with a subsequent contralateral amputation. Conclusions: Patients with advanced PAD that require lower extremity amputation have diminished survival and significant contralateral amputation rates. Elderly patients on dialysis are particularly prone to dying or losing the other leg after a major amputation. These data support strategies to enhance limb preservation and optimize medical comorbidities in these patients.